Improving Meal Break Efficiency Using Six Sigma to Minimize Operational Delay: A Case Study of the Mining Sector in Indonesia - M. Daffa Arafi; Yuliani Dwi Lestari (DINASTI RESEARCH, 2026)
Operational efficiency in mining operations is strongly influenced by effective working time utilization, particularly in shift based systems where equipment productivity directly affects production performance. One significant source of inefficiency is Internal Operational Delay (IOD), especially delays caused by meal break execution. This study investigates the impact of meal break implementation on operational delays and proposes an improvement strategy to enhance efficiency in mining operations in Indonesia. The research applies the Six Sigma DMAIC (Define Measure Analyze Improve Control) methodology to identify, measure, and improve inefficiencies related to meal break activities. Statistical process control using Individuals Moving Range (XmR) charts was employed to assess process variability and stability. Root causes were analyzed using Pareto analysis, Fishbone Diagram, Root Cause Validation, and Cause Prioritization Matrix. The findings reveal that simultaneous meal breaks create a “wave effect,” causing multiple units to become idle simultaneously and reducing equipment utilization. Process-related issues were identified as the most dominant and controllable factors. The proposed improvement is a staggered meal break system, which maintains operational continuity and reduces idle time. The study concludes that optimizing meal break execution can significantly reduce IOD and improve Primary Working Time (PWT), contributing to more stable and efficient mining operations.